Analysis of changes in the hydrological regime in Lalin River basin and its impact on the ecological environment - Wang, Xuege; Ma, Wenchao; Lv, Jun; Li, Hongyan; Liu, Hongchao; Mu, Guangyi; Bian, Dejun (Frontiers in Earth Science, 2022)
Lalin River is a first-level tributary of the right bank of Songhua River. There are high-quality corn production bases irrigated by the Lalin River, such as in Wuchang City, famous throughout the country. With the expansion of the irrigation area, more water was used for irrigation. Due to the increased demand for water resources, the hydrological regimes changed. To investigate the variation of the hydrological situation, we analyzed the daily runoff data at the Caijiagou Hydrological Station from 1954 to 2015 by using the Indicators of Hydrologic Alteration (IHA) and the Range of Variability Approach (RVA). Results showed a severe decreasing trend of the average monthly flows during the water level with regular and high periods, with a negative slope of -2.924 in August and -2.518 in September. Regarding the flow rate, the annual maximum value decreased significantly in slopes of -7.9, -7.6, -6.09, -5.28, and -2.98 on the 1-day, 3-day, 7-day, 30-day, and 90-day. Both the increasing trend of low pulse and fall rate of flow and decreasing trend of the rising rate of flow demonstrate the water resources are drying up. The average value of flow reversals is from 65 to 50 times/year from 1954 to 2015. From RVA analysis, the hydrological alteration of the basin decreased 50% after 1978. To investigate the influencing factors for the hydrological alteration, we analyzed the variation in land cover and land use between 1978 and 2015. Results show that the area of paddy fields in 2015 was 1.5 times that of 1978, and the water consumption in paddy fields accounts for 80.8% of the total water resources. Consequently, the wetland area of the basin in 2015 was only 53% of 1978, and the wetland area of two wetland Nature Reserve at the mouth of Lalin River in 2015 was about 53% of the 1978. Further, The air temperature has shown an intensively increased tendency in the last half-century. On the other hand, the precipitation amount decreased, which is highly possible to lead to river discharge being reduced in the Lalin river, along with the anthropogenic effect.